A systematic review on neutrophils interactions with titanium and zirconia surfaces: Evidence from in vitro studies. Issue 4 (10th May 2022) - Elangovan, Gayathiri; Mello‐Neto, Joao M.; Tadakamadla, Santosh K.; Reher, Peter; Figueredo, Carlos Marcelo S.
Abstract: Objectives: This systematic review aimed to assess in vitro studies that evaluated neutrophil interactions with different roughness levels in titanium and zirconia implant surfaces. Material and Methods: An electronic search for literature was conducted on PubMed, Embase, Scopus, and Web of Science and a total of 14 studies were included. Neutrophil responses were assessed based on adhesion, cell number, surface coverage, cell structure, cytokine secretion, reactive oxygen species (ROS) production, neutrophil activation, receptor expression, and neutrophil extracellular traps (NETs) release. The method of assessing the risk of bias was done using the toxicological data reliability assessment tool (TOXRTOOL). Results: Ten studies have identified a significant increase in neutrophil functions, such as surface coverage, cell adhesion, ROS production, and NETs released when interacting with rough titanium surfaces. Moreover, neutrophil interaction with rough–hydrophilic surfaces seems to produce less proinflammatory cytokines and ROS when compared to naive smooth and rough titanium surfaces. Regarding membrane receptor expression, two studies have reported that the FcγIII receptor (CD16) is responsible for initial neutrophil adhesion to hydrophilic titanium surfaces. Only one study compared neutrophil interaction with titanium alloy and zirconia toughened alumina surfaces and reported no significant differences in neutrophil cell count, activation, receptor expression, and death. Conclusions: There are not enough studies to conclude neutrophil interactions with titanium and zirconia surfaces. However, different topographic modifications such as roughness and hydrophilicity might influence neutrophil interactions with titanium implant surfaces.